Pengaruh Praktik Mawah Terhadap Pendapatan Petani Desa Keulibeut Ulee Tutue Kecamatan Pidie - Muhammad Firdaus; Rauzatul Jannah (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2020)
Abstract Agricultural resources utilization is key in increasing agricultural productivity so that limited resources must be allocated as efficiently as possible. In Aceh there is a model of cooperation in the field of agriculture called Mawah. The purpose of this research is to know the practice and influence of the practices of farmers ' income in the village of Keulibeut Ulee Tutue Pidie District in Pidie district. This research is a quantitative study with a descriptive research approach. The Data obtained is tested for eligibility using validity tests, reliability tests and classic assumption tests. As for the hypotheses test used a simple regression analysis test that includes Test T, Test F and coefficient of determination (R2) test. The results showed that simultaneously there was an overall influence on the practice of the farmer's income from the village Keulibeut Ulee Tutue Pidie Sub District Pidie significantly. It also partially shows that the preactivity is positively and significantly influential for the farmer's income is evidenced in the results of the hypothesis test (T) obtained a value of 0.000 smaller than the prescribed α of 0.05 this means that Ho was rejected and Ha accepted. Keywords: Agricultural, Mawah, Farmers, Income. Abstrak Pemanfaatan sumber daya pertanian adalah kunci dalam meningkatkan produktivitas pertanian sehingga sumber daya yang terbatas harus dialokasikan seefisien mungkin. Di Aceh ada model kerja sama di bidang pertanian yang disebut Mawah. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh praktik mawah terhadap pendapatan petani di Desa Keulibeut Ulee Tutue Kecamatan Pidie di Kabupaten Pidie. Penelitian ini adalah penelitian kuantitatif dengan pendekatan deskriptif. Data yang diperoleh diuji untuk kelayakan menggunakan validitas, reliabilitas dan asumsi klasik. Untuk uji hipotesis digunakan uji analisis regresi sederhana yang meliputi Uji T, Uji F dan uji koefisien determinasi (R2). Hasil penelitian menunjukkan bahwa secara simultan terdapat pengaruh terhadap pendapatan petani dari desa Keulibeut Ulee Tutue Kecamatan Pidie Kecamatan Pidie. Secara parsial menunjukkan bahwa praktik mawah berpengaruh positif dan signifikan terhadap pendapatan petani dibuktikan dalam hasil uji hipotesis (T) diperoleh nilai 0,000 lebih kecil dari α yang ditentukan 0,05 ini berarti Ho ditolak dan Ha diterima. Kata kunci: Pertanian, Mawah, Petani, Penghasilan.